PRINCIPLES OF DEVELOPMENT OF MATHEMATICAL METHODS FOR MODELING PRODUCTION PROCESSES AT THE PRESENT STAGE OF SOCIETY TRANSFORMATION - P. V. Komissarov (Современная наука и инновации)
The study of the development of mathematical methods of production processes at the present epoch of the society's development is one of the most meaningful issues in economic theory. Simulation results' segmentation leads to the requirement to use a huge number of different methods to obtain a comprehensive assessment of the development ofproduction.